Clinical profile of the patients with chronic low back pain - A study of 102 cases - Shakoor, M Abdus; Islam, Md Ariful; Ullah, Md Ahsan; Ahmed, Md Mozaffor; Hasan, Suzon Al (Journal of Chittagong Medical College Teachers’ Association, 2009)
doi: 10.3329/jcmcta.v18i2.3825 Journal of Chittagong Medical College Teachers' Association 2007: 18(2):16-20